Lipid profile in renal transplant recipients receiving immunosuppressive therapy - Lamichhane, Samir; Bajracharya, Sangha Ratna; Shah, Dibya Singh (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Immunosuppression has been detrimental for graft survival in renal transplant recipients (RTRs). Now that acute rejection is less of a concern, the main problem with kidney transplantation is the long term adverse effects of immunosuppression; dyslipidemia and subsequent atherosclerosis leading to cardiovascular diseases being one of them. The objective of the study was to determine the association of lipid profile with immunosuppressive therapy in RTRs. Methods: A descriptive qualitative study was conducted in 120 live RTRs following up at the post-renal transplant clinic in 1 year duration. Means of baseline lipid profiles were compared to those of all follow ups and means of all lipid profiles done at different intervals were compared among different sub-groups of patients grouped according to different variables including the individual immunosuppressants and the immunosuppressive therapy. Results: There was a significant increase in TC levels at 6 and 12 months. HDL-C levels were significantly higher at all follow ups and TG levels done at all follow ups were significantly higher as compared to baseline. LDL-C(12) was significantly higher in the group with higher tacrolimus dose. LDL-C(6), LDL-C(24), TC(24) were significantly different among different prednisolone groups reflecting a relation of prednisolone with alteration in lipid profiles. None of the two regimens was found to be superior over the other regarding lipid profile. Conclusions: This study has shown a significant alteration of lipid profile in patients after renal transplantation as compared to pre-transplant status and immunosuppressive therapy seems to be one among the various contributors to it.